Sex Differences in Cardiovascular Disease Risk and Exercise in Type 2 Diabetes. (1st April 2012) - Miller, Tyler M.; Gilligan, Sarah; Herlache, Leah L.; Regensteiner, Judith G.
Abstract : Diabetes currently affects approximately 14% of the US population, and cardiovascular disease (CVD) is a leading cause of morbidity and mortality in those with diabetes. Although in the general population women are at lower risk than men for CVD, women have a disproportionately greater increase in risk for CVD than do men in the context of diabetes. Physical activity is considered a cornerstone in the prevention and treatment of CVD and its risk factors, but greater barriers to physical activity may exist for women with diabetes compared to their male counterparts. In this article, we review sex differences in CVD incidence and risk among diabetics, sex differences in physical activity behaviors, cardiovascular abnormalities and impaired exercise capacity in women living with diabetes, and the effects of exercise on prevention and treatment of CVD in diabetic women. Finally, we discuss future research needed to clarify potential sex differences in the cardiovascular effects of diabetes and to establish ways to reduce the barriers to exercise in women with diabetes.